Detection of virulence genes in Helicobacter pylori and its correlation with drug resistance by polymerase chain reaction - Chang-Jun Men; Shu-Xuan Shan; Zhen-Yi Ou; Hong-Li Fu; Bei Wang; Yue Tong; Qi Gan; Meng Meng; Ri-Mo Xi (European Journal of Medical Research, 2025)
Abstract Objectives This article aimed to investigate the virulence gene profile of Helicobacter pylori (H. pylori) clinical isolates and explore potential correlations between virulence genes and antimicrobial resistance. Methods Fifty-six H. pylori strains isolated from gastric biopsy specimens were confirmed through biochemical identification (rapid urease test, oxidase test, and urease biochemical reaction). Virulence genes were detected using polymerase chain reaction (PCR). Antimicrobial susceptibility testing against amoxicillin, clarithromycin, levofloxacin, tetracycline, rifampicin, and methicillin was performed via Etest for 41 selected isolates from the original cohort. Results Among Tianjin isolates, oipA and luxS gene demonstrated the highest detection rates (96.43% each). The vacA exhibited vacAs1 (89.29%) and vacAm2 (91.07%) as predominant allelic variants. In contrast, babA2 showed the lowest positivity rate (7.14%), followed by cagA (14.29%). Co-occurrence analysis revealed vacAs1 and luxS gene co-expression in 48 isolates (85.71%), with 96.43% of gastritis patients showing concurrent oipA and luxS gene positivity. Etest results demonstrated no statistically significant association between virulence gene profiles and antibiotic resistance (P > 0.05). Conclusions In this study provides valuable data and insights into the virulence genes and antibiotic resistance of Helicobacter pylori strains isolated from Tianjin, China, to identify potential virulence gene-related biomarkers.